Solving Scheduling Problems with Genetic Algorithms using a Priority Encoding Scheme - Subirats, J.L.; Mesa, Héctor; Ortega-Zamorano, Francisco; Juárez, G.E.; Jerez-Aragonés, José Manuel; Turias, Ignacio; Franco, Leonardo (My University, 2017)
Scheduling problems are very hard computational tasks with several applications in multitude of domains. In this work we solve a practical problem motivated by a real industry situation, in which we apply a genetic algorithm for finding an acceptable solution in a very short time interval. The main novelty introduced in this work is the use of a priority based chromosome codification that determines the precedence of a task with respect to other ones, permitting to introduce in a very simple way all problem constraints, including setup costs and workforce availability. Results show the suitability of the approach, obtaining real time solutions for tasks with up to 50 products.
Keywords: Algoritmos computacionales; Evolutionary and genetic algorithms; Job shop problems; Priority encoding scheme